Revitalization of Pesticide-treated Rice Fields through Local Bacterial Biofilms: An Environmental and Sustainable Agricultural Solution - Rima Permata (Agriculture Journal, 2024)
This study explores the development of Smart Urban Farming 5.0 as an innovative response to energy efficiency and food security issues in Indonesia’s rapidly urbanizing cities. With urban expansion reducing agricultural land, there is a growing need for farming systems that are both space- and energy-efficient. The research focuses on designing and evaluating a vertical farming system that integrates solar panels with automation technologies to boost productivity and reduce dependence on conventional electricity. A prototype system was built using IoT and AI, powered entirely by solar energy, and tested over a three-month period. Key performance indicators included energy consumption, plant growth, and harvest quality. The results revealed a 62% reduction in traditional electricity use and a 28% increase in crop yield, along with lower operational costs compared to conventional farming methods. Although the system requires technical training for operation, user feedback was generally positive. The findings demonstrate that Smart Urban Farming 5.0 can significantly improve the sustainability and efficiency of urban agriculture. This research supports progress toward sustainable development goals, particularly in clean energy and food security, while offering potential for future advancements in intelligent and environmentally friendly urban farming solutions tailored to dense metropolitan areas.